Blockchain Technology and Its Role in Transforming Legal Transactions and Smart Contracts - Ryan Teo; Marcus Tan; Fathurrahman Fathurrahman (Yayasan Adra Karima Hubbi, 2026)
Background. Legal transactions in contemporary digital economies continue to rely on intermediary-driven systems that often generate inefficiencies, delays, and high operational costs. Blockchain technology emerges as an innovative infrastructure capable of transforming conventional legal processes through decentralized verification and automated execution mechanisms. Purpose. This study aims to analyze the role of blockchain technology in transforming legal transactions and smart contracts within modern legal systems. Method. A qualitative-dominant mixed-methods approach is employed using comparative legal analysis, secondary data evaluation, and expert interpretation of blockchain-based contractual systems. Data sources include legal frameworks, blockchain technical documentation, and institutional reports, analyzed through thematic coding and comparative performance assessment. Results. Results indicate that blockchain-based smart contracts significantly reduce transaction processing time from hours to minutes, lower dispute frequency, and improve execution accuracy and transparency compared to traditional legal systems. Inferential findings confirm statistically significant efficiency gains and cost reductions associated with blockchain adoption in legal transactions. Conclusion. The study concludes that blockchain technology fundamentally restructures legal transaction systems by enhancing automation, transparency, and reliability, while still requiring adaptive legal frameworks to address jurisdictional and enforceability challenges in decentralized environments.